The stakeholder balance sheet : profiting from really understanding your market - Suntook, Farrokh (Wiley, 2008)
This book provides an as yet unavailable tool, the Stakeholder Balance Sheet, enablingmanagers within any organisation to unlock the DNA of the market place in which they operate and to measure their effectiveness in understanding their markets and all the key stakeholders operating within them. This simple tool provides self-testing checklists at the end of each chapter that enables managers to look at stakeholder-sensitive issues in the same way that they might scrutinise financial statements (hence it will not seem alien to most managers).